2015
DOI: 10.3390/ijms160921539
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the LPL and CETP Genes and Haplotype in the ESR1 Gene Are Associated with Metabolic Syndrome in Women from Southwestern Mexico

Abstract: Metabolic syndrome (MetS) is a combination of metabolic disorders associated with an increased risk for cardiovascular disease (CVD). Studies in women reported associations between polymorphisms in ESR1, LPL and CETP genes and MetS. Our aim was to evaluate the association between variants in ESR1, LPL and CETP genes with MetS and its components. Four hundred and eighty women were analyzed, anthropometric features and biochemical profiles were evaluated, and genotyping was performed by real-time PCR. We found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
(39 reference statements)
2
13
1
1
Order By: Relevance
“…Our data also suggested that CETP rs820299 was involved in high waist circumference, high triglyceride, and HDL levels. Similarly, previous studies reported that BUD13 rs10790162 21, CETP rs173539 21, and CETP rs708272 24 may contribute to the susceptibility for MetS in European subjects21 and Mexican women24. However, we did not detect an association between BUD13 rs10790162 and MetS in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…Our data also suggested that CETP rs820299 was involved in high waist circumference, high triglyceride, and HDL levels. Similarly, previous studies reported that BUD13 rs10790162 21, CETP rs173539 21, and CETP rs708272 24 may contribute to the susceptibility for MetS in European subjects21 and Mexican women24. However, we did not detect an association between BUD13 rs10790162 and MetS in the present study.…”
Section: Discussioncontrasting
confidence: 66%
“…As described elsewhere (Cahua‐Pablo et al, 2015), the AIMs panel used in this study comprises 104 of the 107 highly informative markers described by Yaeger et al (2008). This panel of markers has been used to characterize admixture proportions in previous studies (Pereira et al, 2012; Risch et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that ESR1 deficiency may result in a risk of insulin resistance and T2DM [27]. ESR1 can suppress lipogenesis in white adipose and liver tissue, enhance insulin sensitivity, and be involved in the maintenance of pancreatic β cells [28,29]. Furthermore, in vitro studies have indicated that ESR1 can modulate insulin receptor substrate 1 [30], caveolin-3 [31], and peroxisome-proliferator activated receptor [32], which are implicated in the molecular mechanisms of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vitro studies have indicated that ESR1 can modulate insulin receptor substrate 1 [30], caveolin-3 [31], and peroxisome-proliferator activated receptor [32], which are implicated in the molecular mechanisms of T2DM. Cahua-Pablo et al [29] held the view that changes in the structure and functionality of ESR1 may result from SNPs in the ESR1 gene. The PvuII and XbaI polymorphisms of ESR1 gene are both located in the first intron, near the gene promoter, indicating that they possibly play a part in the transcription regulation or the processing and stability of mRNA [16].…”
Section: Discussionmentioning
confidence: 99%